Potential thermo-responsive ionic liquid as draw solution in forward osmosis application - Mohd Amirulmukmin, Abdullah; Muhammad Suhaimi, Man; Phang, Sook Nyan; Syed Mohd Saufi, Tuan Chik; Syamsul Bahari, Abdullah (Taylor's University, 2019)
Desalinationbased on membrane technology is one of the approaches which has been extensively explored to tackle the challenge of increasing demand ofclean water. Although reverse osmosis (RO) process has been applied for a long time, the promising forward osmosis (FO) membrane desalination is viewed as a potentially viable energy efficient performancetechnology.But, the main problem in FO process is the lack of suitable draw solutes that can be efficiently regenerated. A distinct advantageusing thermo-responsive ionic liquids (ILs)is the efficient in regenerating the draw solute via thermally stimulation. These draw solutes achieved high water flux 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4])(0.71 LMH) and tetrabutylphosphonium trifluoroacetate ([P4444][CF3COO])(0.44 LMH) compared to NaCl (0.33 LMH). In this research, the phase separation via thermally stimulated liquid-liquid phase separation is achievable.